the integrated curriculum in use practical ideas for planning and assesment barbara mathews and pauline cleary - mathews, b.j.(barbara joan) (ashton scholastic, 1993)
the integrated curriculum in use: practical ideas for planning and assessment is an invaluable tool for teachers who plan to introduce to their classrooms an integrated curriculum